Prevalence of subclinical hypothyroidism in patients of chronic liver disease - Giri, Richa; Singh, Vinay P.; Agarwal, Saurabh; Kumar , Vinay (International Journal of Research in Medical Sciences, 2023)
Background: Chronic liver disease (CLD) is a continuous process of inflammation, destruction, and regeneration of liver parenchyma, which leads to fibrosis and cirrhosis. Liver plays an essential physiological role in thyroid hormone activation and inactivation, transport, and metabolism, as well as the synthesis of thyroid binding globulin. A complex relationship exists between thyroid and liver in health and disease. Methods: 103 patients of CLD were included in this study from December 2020 to September 2022. They were classified as per child Pugh scoring after clinical assessment and investigations. Thyroid function profile was measured for all the patients. Results: Among 103 patients, 8 (7.76%) patients were having overt hypothyroidism and 28 (27.18%) patients had subclinical hypothyroidism, while 67 (65.04%) patients had normal thyroid profile levels. There was significant correlation between CTP class and hypothyroidism status of patient (p value <0.001) with 25 (56.81%) patients of CTP class C having subclinical hypothyroidism, while 3 (7.5%) patients of CTP class B had subclinical hypothyroidism and none patient of CTP class A had subclinical hypothyroidism. Conclusions: Our study found that there was increased prevalence of subclinical hypothyroidism in CLD patients which increased with severity of CLD as assessed with CTP class.